Fine‐scale geographic patterns of gene flow and reproductive character displacement in Drosophila subquinaria and Drosophila recens. Issue 18 (29th August 2018) - Dyer, Kelly A.; Bewick, Emily R.; White, Brooke E.; Bray, Michael J.; Humphreys, Devon P.
Abstract: When two species are incompletely isolated, strengthening premating isolation barriers in response to the production of low fitness hybrids may complete the speciation process. Here, we use the sister species Drosophila subquinaria and Drosophila recens to study the conditions under which this reinforcement of species boundaries occurs in natural populations. We first extend the region of known sympatry between these species, and then we conduct a fine‐scale geographic survey of mate discrimination coupled with estimates of gene flow within and admixture between species. Within D. subquinaria, reinforcement is extremely effective: we find variation in mate discrimination both against D. recens males and against conspecific allopatric males on the scale of a few kilometres and in the face of gene flow both from conspecific populations and introgression from D. recens . In D. recens, we do not find evidence for increased mate discrimination in sympatry, even where D. recens is rare, consistent with substantial gene flow throughout the species' range. Finally, we find that introgression between species is asymmetric, with more from D. recens into D. subquinaria than vice versa. Within each species, admixture is highest in the geographic region where it is rare relative to the other species, suggesting that when hybrids are produced they are of low fitness. In sum, reinforcement within D. subquinaria is effective at maintaining species boundaries, but even when reinforcing selection is strong it may not always result in a pattern of strong reproductive character displacement due to variation in the frequency of hybridization and gene flow from neighbouring populations.